ELAZIĞ'DA YETİŞEN ÇEDENE (PİSTACİA TEREBİNTHUS) BİTKİSİNDE FENOLİK BİLEŞİKLERİN VE BAZI ESER ELEMENTLERİN TAYİNİ - DİNÇ, HİLAL (Fırat Üniveristesi, 2012)
Bu çalışmada, Elazığ ve yöresinden temin edilen çedene (Pistacia terebinthus) ve çedene kahvesinde bulunan bazı fenolik asitler ve flavonoidler ile bazı metallerin konsantrasyonları incelendi. Fenolik madde tayininde HPLC-DAD, metal tayininde alevli AAS cihazları kullanıldı.Fenolik bileşik tayininde çedene bitkisi için bulunan değerler şu şekildedir: vanilik asit: 219,167 ± 26,135 ppm, kafeik asit: 154,5 ± 9,987 ppm, ferulik asit: 9,667 ± 1,04 ppm, rosmarinik asit: (

In this study, the concentration of some phenolic acids, flavonoids and some metals examinated in turpentine and turpentine coffee obtained from Elazig and its surroundings. HPLC-DAD used in determination of phenolic matters, AAS with flame used in determination of metals.These values obtained for turpentine plant in determination of phenolic compounds; vanilic acid: 219,167 ± 26,135 ppm, caffeic acid: 154,5 ± 9,987 ppm, ferulic acid: 9,667 ± 1,04 ppm, rosmarinic acid: (< t.s), quercetin: 156,83 ± 11,85 ppm, resveratrol: 373,5 ± 19,15 ppm.These values obtained for turpentine coffee in determination of phenolic compounds; vanilic acid 179,5 ± 13,4 ppm, caffeic acid 101,5 ± 8,4 ppm, ferulic acid 3,5 ± 0,5 ppm, resveratrol 295,41 ± 20,05 ppm, quercetin 129,9 ± 10,3 ppm.These values obtained in determination of metals with microwave digestion method: Cu (
Determination of phenolic compounds and trace elements in turpentine (Pistacia terebinthus) grown in Elazig
Keywords: Kimya